Lightweight aluminum alloy material, preparation method thereof and application of lightweight aluminum alloy material in new energy automobile
By optimizing element composition and adding nano silicon carbide, refining grains, and improving the mechanical and corrosion resistance of aluminum alloy materials, the problem of insufficient hardness and corrosion resistance of aluminum alloy materials in new energy vehicles is solved, providing safer and more efficient battery protection.
Patent Information
- Application Number
- CN202411122796.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The aluminum alloy materials used in existing new energy vehicles have insufficient hardness and fatigue resistance, which are easily pierced by sharp objects, and have poor corrosion resistance, which affects battery safety.
By optimizing the element composition, adding a small amount of transition elements and nano silicon carbide, refining the grains, improving the mechanical properties and corrosion resistance of the material, a lightweight aluminum alloy material is prepared using specific preparation methods and surface treatment techniques.
It significantly improves the mechanical properties and corrosion resistance of aluminum alloy materials, and is suitable for use in motor housings, battery housings and other parts of new energy vehicles, enhances the protection capacity of the battery and reduces the body quality.
Smart Images

Figure CN119320896A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel aviation aluminum alloy materials, and specifically relates to a lightweight aluminum alloy material and a preparation method thereof and an application in new energy vehicles. Background Art
[0002] As global climate change and environmental pollution problems gradually intensify, new energy vehicles have become an energy-saving and environmentally friendly way of travel. The emergence of new energy vehicle types such as electric vehicles, hybrid vehicles and fuel cell vehicles indicates that the automotive industry is moving towards a cleaner and more sustainable direction. However, the battery weight of new energy vehicles has always been the main condition limiting their performance and range. The weight of the battery system not only affects the vehicle's power performance, but also leads to a decrease in energy efficiency, limiting the popularity of new energy vehicles.
[0003] As global attention to environmental protection and energy sustainability continues to increase, lightweight design of new energy vehicles has become a hot topic in the automotive industry. Lightweight design aims to reduce the overall weight of the vehicle to improve driving range, increase energy efficiency, and reduce dependence on limited resources.
[0004] At present, the lightweight design of new energy vehicles is mainly carried out around two aspects: innovative material design and structural optimization. Carbon fiber composite materials, aluminum alloys, magnesium alloys and high-strength steel are used. These materials have low density and excellent strength, which help to reduce the weight of the car. In the lightweight design of new energy vehicles, aluminum alloys are widely used to manufacture key components of engines and transmission systems, such as engine cylinders, crankcases, transmission housings, etc. Compared with traditional iron materials, aluminum alloys have lower density, which can effectively reduce the burden on the power system and improve fuel efficiency. In addition, aluminum alloys have excellent thermal conductivity, which helps to dissipate heat and improve engine performance and reliability.
[0005] Existing battery trays, battery shells and other materials are mainly made of aluminum alloy materials, but the hardness and fatigue resistance of the current materials are relatively insufficient. When used as battery shell materials, they are easily pierced by sharp objects, which can damage the internal battery structure, cause leakage or short circuit, and even cause the car to catch fire. At the same time, the overall corrosion resistance of the material is poor. After long-term use, structural defects are prone to occur, which significantly reduces the protection of the internal battery cells, thereby affecting the safety of electric vehicles.
[0006] Therefore, how to develop a lightweight aluminum alloy material with excellent mechanical properties and high corrosion resistance has positive significance for accelerating the high-quality development of new energy vehicles, and it is also a technical problem that needs to be solved urgently. Summary of the invention
[0007] The present invention aims to solve the problems existing in the prior art by optimizing the elemental composition and adding a small amount of transition elements and nano-silicon carbide to effectively refine the grains, increase the density of the system, and significantly improve the mechanical properties and corrosion resistance of the material, thereby meeting the use requirements in the field of new energy vehicles.
[0008] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0009] A light aluminum alloy material comprises the following components by mass percentage: 0.6-1.8% magnesium, 0.3-0.5% manganese, 0.2-0.5% copper, 0.1-0.3% zinc, 0.1-0.5% transition element combination, 0.04-0.06% chromium, 0.01-0.05% strontium, 0.01-0.02% titanium, 0.1-0.3% nano silicon carbide, and the remainder is aluminum and impurities, wherein the total amount of impurities is no more than 0.1%, and the total amount is 100%.
[0010] Preferably, the transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:1.
[0011] Preferably, the preparation method of the nano silicon carbide is: starch, nano silica sol and water are placed in a container, heated and stirred at 80-90°C until they are in a gel state, then naturally cooled and freeze-dried, ball-milled to obtain a solid powder, and the solid powder is calcined at 1200-1300°C for 3-6h under nitrogen protection, and then placed in a muffle furnace for calcination at 500-600°C for 3-4h and then naturally cooled, and the calcined solid powder is then immersed in 1M hydrofluoric acid, left to stand for 5-10h, and then repeatedly rinsed with deionized water until neutral, and dried and ground.
[0012] More preferably, the mass ratio of the starch, nano-silica sol and water is 3:10:40; and the average particle size of the silica sol is 20-50 nm.
[0013] More preferably, the solid-liquid ratio of the calcined solid powder to hydrofluoric acid is 1 g:10 mL.
[0014] A method for preparing a lightweight aluminum alloy material comprises the following preparation steps:
[0015] (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion;
[0016] (2) Preparation of nano-silicon carbide;
[0017] (3) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or a medium frequency furnace for melting. Heat it until it is completely melted and keep it warm for 20-30 minutes. Then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium element raw materials, and finally add nano silicon carbide. The melting temperature is controlled between 750-760°C. Argon is used for protection during the melting process. After the metal is completely melted, it is refined, slag removed, and cast in sequence to obtain an aluminum alloy casting.
[0018] (4) Surface treatment: After the aluminum alloy casting is placed in boiling water for 20-30 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 10-20 minutes, and then dried after the treatment is completed.
[0019] Preferably, after the casting is prepared in step (3), quenching and tempering treatment is also included: the quenching temperature is 700-800°C, the temperature is lowered after quenching, and then tempering treatment is performed, and the tempering temperature is 200-220°C.
[0020] Preferably, the mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 5-10%.
[0021] A lightweight aluminum alloy material is used. The obtained aluminum alloy material can be used to manufacture motor housings, battery housings, and battery tray components of new energy vehicles, and can also be used in vehicle frames and other parts. It can not only reduce the weight of the vehicle body, but also has excellent mechanical properties and corrosion resistance, effectively protecting the battery.
[0022] Beneficial effects:
[0023] (1) The present invention adds trace amounts of transition metals scandium, molybdenum, and niobium to the main body of aluminum. Scandium is the most effective grain refiner for aluminum and aluminum alloys. By adding a small amount of scandium, the grain size of the cast alloy can be significantly reduced, thereby enhancing the strength and toughness of the aluminum alloy. At the same time, scandium can inhibit the recrystallization process, thereby significantly improving the corrosion resistance of the aluminum alloy. Molybdenum can significantly improve the strength and hardness of aluminum alloys, and improve their heat resistance and corrosion resistance. Niobium can increase ductility, wear resistance, and impact resistance in aluminum alloys. When used in combination with scandium and molybdenum in equal proportions, a synergistic effect is produced, and grain refinement is more significant, which can further improve the comprehensive performance of aluminum alloys.
[0024] (2) On the other hand, the present invention adds metal elements such as strontium, titanium, copper, and magnesium. The solid solution strengthening brought by Cu and Mg elements gives the alloy excellent mechanical properties. In addition, the addition of strontium, titanium, and other elements gives the alloy good corrosion resistance and thermal conductivity.
[0025] (3) The present invention uses starch and nano-silica sol to prepare inorganic nanomaterials, which are finally added to the aluminum melt. They have a high melting point and elastic modulus, which enables them to maintain high thermal stability and deformation stability at high temperatures. Introducing these inorganic nanoparticles into aluminum alloys can effectively refine the grains, enhance the microstructure of the material, increase the density of the system, and thus significantly improve its stiffness and strength.
[0026] (4) On the basis of effectively improving the grain refinement of the system, the present invention uses octadecyl trimethoxysilane toluene for surface treatment. Under the impact of bubbles of high-temperature boiling water, the surface structure of the aluminum profile is further refined to form a finer and rougher micro-nano villi structure. Such a structure can stably store a large amount of air, form an air cushion between the sample surface and the corrosive medium, slow down corrosion, and is also more conducive to the subsequent modification of octadecyl trimethoxysilane toluene, forming a super-hydrophobic surface, reducing the attachment of moisture and various corrosive matrices, and further improving the material's corrosion resistance.
[0027] (5) In summary, the present invention optimizes the elemental composition and adds inorganic nanoparticles to effectively refine the grains and improve the density of the system, and with the assistance of efficient surface treatment methods, the obtained aluminum alloy material has good comprehensive mechanical properties and corrosion resistance. It is suitable for use in new energy vehicle battery shells, battery guards and other parts to effectively protect the battery. It is also suitable for use in parts such as vehicle frames and is lightweight and durable. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the tensile test specimen;
[0029] Figure 2 This is an electron microscope image of the fracture morphology of the tensile specimen in the test of Example 3 of the present invention;
[0030] Figure 3 This is an electron microscope image of the fracture morphology of the tensile test specimens of Comparative Examples 1-9 of the present invention;
[0031] Figure 4 This is an electron microscope image of the fracture morphology of the tensile test specimen of Comparative Example 10 of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0033] Example 1
[0034] A light aluminum alloy material comprises the following components, measured by mass percentage: 0.6% magnesium, 0.3% manganese, 0.5% copper, 0.3% zinc, 0.1% transition element combination, 0.04% chromium, 0.01% strontium, 0.01% titanium, 0.1% nano silicon carbide, and the remainder is aluminum and impurities, wherein the total amount of impurities is no more than 0.1%, and the total amount is 100%.
[0035] The transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:1.
[0036] The preparation method of the nano silicon carbide is as follows: starch, nano silica sol and water are placed in a container, heated and stirred at 80-90° C. to a gel state, then naturally cooled and freeze-dried, ball-milled to obtain a solid powder, calcined the solid powder at 1200° C. for 3 hours under nitrogen protection, then placed in a muffle furnace for calcination at 500° C. for 3 hours and then naturally cooled, then the calcined solid powder is immersed in 1M hydrofluoric acid, left to stand for 5 hours, repeatedly rinsed with deionized water until neutral, and dried and ground.
[0037] The mass ratio of the starch, nano-silica sol and water is 3:10:40; the average particle size of the silica sol is 20-50 nm.
[0038] The solid-liquid ratio of the calcined solid powder to hydrofluoric acid is 1 g:10 mL.
[0039] A method for preparing a lightweight aluminum alloy material comprises the following preparation steps:
[0040] (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion;
[0041] (2) Preparation of nano-silicon carbide;
[0042] (3) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or a medium frequency furnace for melting, heat it until it is completely melted and keep it warm for 20 minutes; then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium element raw materials, and finally add nano silicon carbide. The melting temperature is controlled between 750-760°C. Argon gas is used for protection during the melting process. After the metal is completely melted, it is refined, slag removed, and cast in sequence to obtain an aluminum alloy casting.
[0043] (4) Surface treatment: After the aluminum alloy casting is placed in boiling water for 20 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 10 minutes and then dried after the treatment is completed.
[0044] After the casting is prepared in step (3), quenching and tempering treatment are also included: the quenching temperature is 700°C, the temperature is lowered after quenching, and then tempering is performed, and the tempering temperature is 200°C.
[0045] The mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 5%.
[0046] Example 2
[0047] A light aluminum alloy material comprises the following components, measured by mass percentage: 1% magnesium, 0.4% manganese, 0.3% copper, 0.2% zinc, 0.3% transition element combination, 0.04% chromium, 0.03% strontium, 0.02% titanium, 0.2% nano silicon carbide, and the remainder is aluminum and impurities, wherein the total amount of impurities is no more than 0.1%, and the total amount is 100%.
[0048] The transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:1.
[0049] The preparation method of the nano silicon carbide is as follows: starch, nano silica sol and water are placed in a container, heated and stirred at 80-90° C. to a gel state, then naturally cooled and freeze-dried, ball-milled to obtain a solid powder, calcined the solid powder at 1200° C. for 4 hours under nitrogen protection, then placed in a muffle furnace for calcination at 600° C. for 4 hours and then naturally cooled, then the calcined solid powder is immersed in 1M hydrofluoric acid, left to stand for 6 hours, repeatedly rinsed with deionized water until neutral, and dried and ground.
[0050] The mass ratio of the starch, nano-silica sol and water is 3:10:40; the average particle size of the silica sol is 20-50 nm.
[0051] The solid-liquid ratio of the calcined solid powder to hydrofluoric acid is 1 g:10 mL.
[0052] A method for preparing a lightweight aluminum alloy material comprises the following preparation steps:
[0053] (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion;
[0054] (2) Preparation of nano-silicon carbide;
[0055] (3) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or a medium frequency furnace for melting, heat it until it is completely melted and keep it warm for 30 minutes; then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium element raw materials, and finally add nano silicon carbide. The melting temperature is controlled between 750-760°C. Argon gas is used for protection during the melting process. After the metal is completely melted, it is refined, slag removed, and cast in sequence to obtain an aluminum alloy casting.
[0056] (4) Surface treatment: After the aluminum alloy casting is placed in boiling water for 20 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 20 minutes, and then dried after the treatment is completed.
[0057] Step (3) includes quenching and tempering treatment after the casting is completed: the quenching temperature is 800°C, the temperature is lowered after quenching, and then tempering is performed, and the tempering temperature is 200°C.
[0058] The mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 7%.
[0059] Example 3
[0060] A lightweight aluminum alloy material comprises the following components, measured by mass percentage: 1.8% magnesium, 0.5% manganese, 0.2% copper, 0.3% zinc, 0.5% transition element combination, 0.06% chromium, 0.05% strontium, 0.02% titanium, 0.3% nano silicon carbide, and the remainder is aluminum and impurities, wherein the total amount of impurities is no more than 0.1%, and the total amount is 100%.
[0061] The transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:1.
[0062] The preparation method of the nano silicon carbide is as follows: starch, nano silica sol and water are placed in a container, heated and stirred at 80-90° C. to a gel state, then naturally cooled and freeze-dried, ball-milled to obtain a solid powder, calcined the solid powder at 1300° C. for 6 hours under nitrogen protection, calcined at 600° C. for 4 hours in a muffle furnace, and then naturally cooled, and then the calcined solid powder is immersed in 1M hydrofluoric acid, left to stand for 10 hours, repeatedly rinsed with deionized water until neutral, and dried and ground.
[0063] The mass ratio of the starch, nano-silica sol and water is 3:10:40; the average particle size of the silica sol is 20-50 nm.
[0064] The solid-liquid ratio of the calcined solid powder to hydrofluoric acid is 1 g:10 mL.
[0065] A method for preparing a lightweight aluminum alloy material comprises the following preparation steps:
[0066] (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion;
[0067] (2) Preparation of nano-silicon carbide;
[0068] (3) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or a medium frequency furnace for melting, heat it until it is completely melted and keep it warm for 30 minutes; then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium element raw materials, and finally add nano silicon carbide. The melting temperature is controlled between 750-760°C. Argon gas is used for protection during the melting process. After the metal is completely melted, it is refined, slag removed, and cast in sequence to obtain an aluminum alloy casting.
[0069] (4) Surface treatment: After the aluminum alloy casting is placed in boiling water for 30 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 20 minutes and then dried after the treatment is completed.
[0070] After the casting is prepared in step (3), quenching and tempering treatment are also included: the quenching temperature is 800°C, the temperature is lowered after quenching, and then tempering is performed, and the tempering temperature is 220°C.
[0071] The mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 10%.
[0072] Comparative Examples 1-9
[0073] The dosage ratio of the transition element combination was changed to set a comparative example, and the remaining raw materials and preparation method were the same as those in Example 3. Specifically:
[0074] Table 1 Comparative proportion of transition element combination dosage relationship
[0075] scandium molybdenum niobium Comparative Example 1 0 1 1 Comparative Example 2 1 0 1 Comparative Example 3 1 1 0 Comparative Example 4 1 0 0 Comparative Example 5 0 1 0 Comparative Example 6 0 0 1 Comparative Example 7 2 1 1 Comparative Example 8 1 2 1 Comparative Example 9 1 1 2
[0076] Comparative Example 10
[0077] A lightweight aluminum alloy material comprises the following components, measured by mass percentage: 1.8% magnesium, 0.5% manganese, 0.2% copper, 0.3% zinc, 0.5% transition element combination, 0.06% chromium, 0.05% strontium, 0.02% titanium, and the remainder being aluminum and impurities, wherein the total amount of impurities is no more than 0.1%, and the total amount is 100%.
[0078] The transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:1.
[0079] A method for preparing a lightweight aluminum alloy material comprises the following preparation steps:
[0080] (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion;
[0081] (2) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or medium frequency furnace for melting, heat it until it is completely melted and keep it warm for 30
[0082] minutes; then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, and titanium raw materials, control the smelting temperature between 750-760°C, use argon protection during the smelting process, and after all the metals are melted, they are refined, slag removed, and cast in sequence to obtain aluminum alloy castings.
[0083] (3) Surface treatment: After the aluminum alloy casting is placed in boiling water for 30 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 20 minutes and then dried after the treatment is completed.
[0084] After the casting is prepared in step (3), quenching and tempering treatment are also included: the quenching temperature is 800°C, the temperature is lowered after quenching, and then tempering is performed, and the tempering temperature is 220°C.
[0085] The mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 10%.
[0086] In this comparative example, except that the raw materials do not contain nano-silicon carbide, the other raw materials and preparation method are the same as those of Example 3.
[0087] Performance Testing
[0088] The aluminum alloy materials obtained in Examples 1-3 of the present invention and Comparative Documents 1-9 were tested, and dumbbell-shaped tensile specimens were cast, which met the requirements of the national standard GB / T228.1-2021. Figure 1 The tensile properties and Brinell hardness of the aluminum alloy were tested by a tensile testing machine (Intsron3369) and a hardness tester (220HBS-3000).
[0089] Contact angle test: The contact angle between the sample and water was measured using a JY-82 video contact angle tester from Chengde, China.
[0090] Fracture morphology observation: The fracture morphology of the tensile fracture specimens was observed using a S-3400N scanning electron microscope to determine the fracture mode of the alloy under the test conditions.
[0091] Electrochemical test: The samples were tested using a CHI600E electrochemical workstation produced by Shanghai Chenhua Company. A standard three-electrode system was used in the experiment, with the working electrode being the sample to be tested, the reference electrode being the calomel electrode, and the auxiliary electrode being the platinum electrode. A 3.5% NaCl aqueous solution was prepared as the corrosion medium (a 3.5% NaCl aqueous solution simulated the state of seawater), and the working electrode area was 3.14 cm 2 , the voltage test range is -2-0V, and the potential scanning rate is 3mV / s.
[0092] All test results were repeated 5 times and the average value was taken.
[0093] Test results table
[0094] Table 2 Mechanical properties test results
[0095]
[0096]
[0097] Table 3 Self-corrosion current density and corrosion potential of samples
[0098] <![CDATA[Icorr(A / cm 2 ,×10 -6 )]]> Ecorr(V) Example 1 1.9 -0.505 Example 2 1.8 -0.481 Example 3 1.8 -0.452 Comparative Example 1 2.8 -0.631 Comparative Example 2 2.9 -0.645 Comparative Example 3 2.9 -0.642 Comparative Example 4 3.2 -0.712 Comparative Example 5 3.1 -0.709 Comparative Example 6 3.3 -0.725 Comparative Example 7 2.3 -0.612 Comparative Example 8 2.2 -0.602 Comparative Example 9 2.4 -0.618 Comparative Example 10 5.1 -0.892
[0099] From the data in Table 2-3, we can see that the examples of the present invention present good mechanical properties and corrosion resistance. The higher the corrosion potential, the lower the tendency to corrosion. The current density reflects the corrosion rate. The smaller the current density, the slower the corrosion rate. However, the mechanical properties and corrosion resistance of Comparative Examples 1-10, which have changed the element composition and raw material composition, have weakened to varying degrees. This is because the refinement effect of the matrix in Comparative Examples 1-9, which have changed the transition element composition, and the synergistic balance effect is broken, which leads to a decrease in mechanical properties and corrosion resistance. It can be seen that the addition of transition element composition and nano-silicon carbide in the present invention is critical to the improvement of the comprehensive performance of aluminum alloy materials. If one is missing, the effect will be weak. From the fracture morphology of the sample, it can be seen that the tensile fracture of Example 3 of the present invention presents a large number of fine dimple structures, and no obvious cleavage plane is found. The fracture mode is a typical ductile fracture. The morphology of the comparative example is relatively poor.
[0100] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A lightweight aluminum alloy material, characterized in that: Calculated by mass percentage, the invention comprises the following components: 0.6-1.8% magnesium, 0.3-0.5% manganese, 0.2-0.5% copper, 0.1-0.3% zinc, 0.1-0.5% transition element combination, 0.04-0.06% chromium, 0.01-0.05% strontium, 0.01-0.02% titanium, 0.1-0.3% nano silicon carbide, and the remainder is aluminum and impurities, wherein the total amount of impurities is not more than 0.1%, and the total amount is 100%.
2. The lightweight aluminum alloy material according to claim 1, characterized in that: The transition element combination includes scandium, molybdenum and niobium, and the mass ratio of the three is 1:1:
1.
3. The lightweight aluminum alloy material according to claim 1, characterized in that: The preparation method of the nano silicon carbide is as follows: starch, nano silica sol and water are placed in a container, heated and stirred at 80-90° C. to a gel state, then naturally cooled and freeze-dried, ball-milled to obtain a solid powder, calcined the solid powder at 1200-1300° C. for 3-6 hours under nitrogen protection, then placed in a muffle furnace for calcination at 500-600° C. for 3-4 hours and then naturally cooled, then the calcined solid powder is immersed in 1M hydrofluoric acid, left to stand for 5-10 hours, repeatedly rinsed with deionized water until neutral, and dried and ground.
4. The lightweight aluminum alloy material according to claim 3, characterized in that: The mass ratio of the starch, nano-silica sol and water is 3:10:40; the average particle size of the silica sol is 20-50 nm.
5. The lightweight aluminum alloy material according to claim 3, characterized in that: The solid-liquid ratio of the calcined solid powder to hydrofluoric acid is 1 g:10 mL.
6. A method for preparing the lightweight aluminum alloy material according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: (1) Material preparation: preparing magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium and aluminum metal raw materials according to the proportion; (2) Preparation of nano-silicon carbide; (3) After cleaning the main aluminum material, place the aluminum ingot in a melting furnace or a medium frequency furnace for melting. Heat it until it is completely melted and keep it warm for 20-30 minutes. Then add magnesium, manganese, copper, zinc, transition element combination, chromium, strontium, titanium element raw materials, and finally add nano silicon carbide. The melting temperature is controlled between 750-760°C. Argon is used for protection during the melting process. After the metal is completely melted, it is refined, slag removed, and cast in sequence to obtain an aluminum alloy casting. (4) Surface treatment: After the aluminum alloy casting is placed in boiling water for 20-30 minutes, it is immersed in octadecyltrimethoxysilane toluene solution for 10-20 minutes, and then dried after the treatment is completed.
7. The method for preparing a lightweight aluminum alloy material according to claim 6, characterized in that: After the casting is prepared in step (3), quenching and tempering treatment are also included: the quenching temperature is 700-800°C, the temperature is lowered after quenching, and then tempering treatment is performed, and the tempering temperature is 200-220°C.
8. The method for preparing a lightweight aluminum alloy material according to claim 6, characterized in that: The mass concentration of the octadecyltrimethoxysilane toluene solution in step (4) is 5-10%.
9. An application of the lightweight aluminum alloy material according to any one of claims 1 to 5, characterized in that: The obtained aluminum alloy material is used to manufacture battery cases and battery tray components for new energy vehicles.
Citation Information
Patent Citations
Preparation method of aluminum-based composite material
CN104357691A
Method for producing aluminum profile
CN104694798A
Composite material having improved mechanical properties at elevated temperatures
CN107532248A
High-strength corrosion-resistant passenger car battery box
CN107760162A
Novel aluminum alloy door and window sectional material and preparation method thereof
CN108441715A